Routine coagulation molecules predict nasopharyngeal carcinoma and associated metastases. Issue 4 (2nd October 2019) - Yin, J; Zhu, SS
ABSTRACT: Introduction : Most patients with malignant solid tumours have abnormal blood coagulation and an abnormal peripheral blood count, but data on nasopharyngeal carcinoma is scare. We hypothesised abnormal coagulation indices and red cell distribution width (RDW) in this group that are linked to the tumour (T), lymph node (N) and metastatic aspects (M) of the patients. Methods : We recruited 740 newly diagnosed patients with nasopharyngeal carcinoma and 238 healthy controls, taking venous blood for prothrombin time, activated partial thromboplastin time (APTT), thrombin time, fibrinogen, fibrin degradation products (FDP), D-dimer, RD), platelets and platelet distribution width (PDW). In the patients, lab indices were analysed according to clinical stage. Results : All indices except thrombin time were significantly different between cases and controls ( p < 0.001), and many predicted TNM classifications and early or late stage of the disease. In sensitivity/specificity analysis, the prothrombin time, APTT and PDW gave AUCs >0.7, and in combination gave an AUC of 0.88 (95% CI 0.86–0.91) for nasopharyngeal carcinoma. No index provided an AUC >0.7 for T or N classification, or early v late stage, but APTT, fibrinogen and FDP all gave AUCs ≥0.7 for predicting metastases. Together, these three indices gave an AUC of 0.84 (0.78–0.91). Conclusions : Routine coagulation indices can predict nasopharyngeal carcinoma, with the combination of prothrombin time, APTT and PDW being strongest. The combination of APTT, fibrinogen and FDPs provides a useful score to predict metastases. These indices should be considered in the diagnosis and staging of this disease.